Informasi Akuntansi Manajemen, Sistem Pengukuran Kinerja, dan Penghargaan Terhadap Kinerja Manajerial - Salsabila Salsabila; Hendra Hermain; Laylan Syafina (Journal of Management and Bussines (JOMB), 2023)
In order for a corporation to succeed in achieving its goals, the company will often work to improve the performance of its management. Managers' performance can be influenced by various elements, the most important of which are management accounting information, performance appraisal methods, and incentives. The final result of this study is to find out whether or not these elements influence the performance of management positions. PT.Perkebunan Milano Aek Batu is part of the Wilmar group which is the location where this research was conducted. Sampling for this study was carried out using a purposive sampling approach. The information collected for this study was taken directly from the questionnaire responses given to PT.Perkebunan Milano Aek Batu workers as the population in this study. In accordance with the specifications that have been mentioned, obtained as many as 97 employees as research samples. The findings of the study revealed that the elements suspected of influencing management performance were proven to have an effect partially and simultaneously. Keywords: Managerial Performance, Management Accounting Information, Performance Measurement System, Rewards